1998
DOI: 10.1002/qj.49712455215
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐hemispheric oceanic exchange

Abstract: SUMMARYThe exchange of water between hemispheres is examined theoretically by looking at the behaviour of continuous (double frontal) abyssal currents situated on the bottom of a (parabolic) meridional channel. We used a reduced-gravity (fluid) model with an active lower layer on the bottom of the channel, and a passive infinitely deep upper layer on the top. The topography is the agent responsible for forcing the current across the equator. We first examined analytically the nonlinear, steady, frictionless ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…The important distinction between the two models is that the lack of inertial terms in the FG model severely restricts the motion of the fluid, whereas the shallow water model has inertial terms available when needed. This is entirely consistent with the conclusions of Nof andBorisov [1998] (andRodwell andHoskins [2001], for atmospheric equatorcrossing flows), who found that equator-crossing flow is primarily an inertial process, with the topography interacting strongly with the flow, but the presence of friction was necessary to modify potential vorticity as the fluid moved between hemispheres.…”
Section: Discussionsupporting
confidence: 90%
“…The important distinction between the two models is that the lack of inertial terms in the FG model severely restricts the motion of the fluid, whereas the shallow water model has inertial terms available when needed. This is entirely consistent with the conclusions of Nof andBorisov [1998] (andRodwell andHoskins [2001], for atmospheric equatorcrossing flows), who found that equator-crossing flow is primarily an inertial process, with the topography interacting strongly with the flow, but the presence of friction was necessary to modify potential vorticity as the fluid moved between hemispheres.…”
Section: Discussionsupporting
confidence: 90%
“…Nof and Borisov [16] compared the numerical simulations of double frontal currents on a parabolic meridional channel using a reducedgravity shallow-water model to the solid particles of Borisov and Nof [16] and to the analytic solution of Nof and Olson [17]. Since the shallow-water simulations compared favorably with the dynamics of the solid particles, Nof and Borisov [16] concluded that the equatorcrossing process is an inertial one where the geometry of the bottom topography plays a crucial role.…”
mentioning
confidence: 99%
“…Since the shallow-water simulations compared favorably with the dynamics of the solid particles, Nof and Borisov [16] concluded that the equatorcrossing process is an inertial one where the geometry of the bottom topography plays a crucial role. The differences between the inviscid analytic solutions of Nof and Olson [17], where potential vorticity is conserved, and the viscous shallow water simulations led them to conclude that the potential vorticity is modified by friction as the current proceeds, allowing the flow to propagate along the path prescribed by the bottom topography.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the theoretical question arises concerning the dynamical balances that govern the equatorial dynamics of these abyssal flows. The oceanographic data clearly shows that these flows cross the equator and circulate around the entire the globe [3].…”
Section: Introductionmentioning
confidence: 98%